Spectrophotometer for atmospheric ozone research – receiver reaction of irradiation with complex spectral composition - Stoyanov, S. (Економіка природокористування і охорони довкілля, 2013)
One of the basic problems in elaboration of spectro-photometer for atmospheric ozone research at the Space Research and Technologies Institute – Bulgarian Academy of Sciences seems to be the necessity of calculation of output signal of the irradiating receiver by fixed spectral composition and intensity. The calculation wouldn’t be difficult if the intensity values range is situated on the linear part of the irradiating receiver energetic characteristic. To the end, the absolutely spectral characteristic of receiver sensibility and spectral density of the treated receiver intensity has to be known.
The paper is dedicated to the elaboration and the obtained results by offering and creating a method for definition of the irradiating receiver output signal by fixed spectral composition and intensity
In the paper presents the obtained schemes and equations in the process of elaboration characterizing the reaction of the photo-receiver complex spectral composition with nonlinear energetic characteristic.